Empire-Building, Imperial Policies, and Famine in Occupied Territories and Colonies - Klid, Bohdan (East/West, 2021)
The introductory article to the special issue “Empire, Colonialism, and Famine in the Nineteenth and Twentieth Centuries” begins by pointing to some recent literature on famine theory, where stress has been made on responses of authorities to famine and on the political nature of modern famines. Literature on the connection between imperial policies, colonial rule, and famines is also briefly discussed. The Soviet Union is treated as an empire in the essay, and some of the literature on this question is also surveyed. The article then offers summaries of and highlights from essays in this volume that resulted from papers presented at two conferences on the theme “Empires and Famines in Comparative Historical Perspective,” held in 2016 in Toronto and in 2017 in Kyiv. These include papers on famine and food policies during World War II in occupied Ukraine and Moldova. Essays on famines in Soviet Ukraine, British-ruled Ireland, and British-ruled Bengal, India, are summarized as well as an essay on Raphaël Lemkin’s views on genocide and famine and an essay that looked at minorities in Mao’s China during the 1958-62 famine. The essay concludes with the observation that the investigation of imperial policies, colonial rule, and famine should be pursued further, especially in the case of the Soviet Union where this line of research is just beginning.